Boom or gloom : performance of the SES all-property index - Goh, Ruby Wee Poh (2015)
The inspiration for this research is two-fold: First being the intense media attention accorded to the property sector throughout 1993, especially the mind-boggling prices of real estate transactions; and the second being what appears to be a spiralling rise in property stock prices. The motivation is to attempt to gauge the property sector performance via a more focused approach-namely, an empirical survey of property stock performance on the Stock Exchange of Singapore (SES). The most intriguing question in mind has been: To what extent does boom or gloom prevail in the property sector? A study is made on the performance of the SES All-Property Index and 4 selected property stocks (viz ., DBS Land Ltd., UOL Ltd ., Malayan Credit Ltd. and City Developments Ltd.) relative to the SES All-Singapore Index-the market surrogate. Investigation spans 15.5 years from January 1978-June 1993, partitioned into 3 shorter sub-periods (1978-1982, 1983-1987, 1988-June 1993) for scrutiny. In particular, the most current sub-period will be the period of focus for the 4 property stocks reviewed. The methodology involves regression analysis of relevant share indices and adjusted share prices, results of which are used in computing 3 risk-adjusted performance measures: the Jensen, Treynor and Sharpe Indices. The main regression of 15.5 years sees the property sector outperforming the market marginally for the period. Over-performance are registered for the first and final sub-periods while under-performance occurred in the middle sub-period. Regression statistics suggest that general market conditions and macroeconomic factors have telling effects on sector performance. Individual property stocks returned mixed results for the period from 1988-June 1993: 3 stocks (DBS Land Ltd., Malayan Credit Ltd., and City Developments Ltd.) out-performed the market while UOL Ltd. under-performed. This suggests that performance can be inconsistent over the same period within the sector. Prior to the publication of this paper, the opportunity arose for the extension of the review period to 31 December 1993. Simple percentage increases were computed for the market and sector indices, and the adjusted share prices of the 4 property stocks. While the market index has risen some 40% since 30 June 1993, the sector index has raced ahead with a 78% increase. The individual property stocks are not to be outdone, rising between 52-85%. As the Jensen, Treynor and Sharpe Indices were not computed thereon to measure actual performance, these results can only be indicative of trend. The property sector is shown to have out-performed the market over the last 15.5 years--a financially rewarding experience for any investor in property stocks during the period. If the rising trend persists, as recent results are apt to suggest, then boom will reign yet in the property sector for time to come.